Service Quality, Price, and Customer Satisfaction Impact on Customer Loyalty: Evidence from a Furniture Retail Study: Kualitas Layanan, Harga, dan Kepuasan Pelanggan Mempengaruhi Loyalitas Pelanggan: Bukti dari Studi Ritel Perabotan - Alfaris Sururi; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative research study investigates the influence of service quality, price, and customer satisfaction on customer loyalty within the context of a furniture retail establishment. A purposive sampling method was employed, involving 100 consumers of the retail store. Data were collected through questionnaires and analyzed using SPSS statistical software (version 25). The findings affirm that service quality, price, and customer satisfaction significantly impact customer loyalty, highlighting their pivotal roles in shaping consumer behavior. These results offer valuable insights for businesses seeking to enhance customer loyalty and, by extension, improve their competitiveness in the global marketplace. Highlights: Key Findings: Service quality, price, and customer satisfaction are crucial determinants of customer loyalty in the retail sector. Methodology: Quantitative research using SPSS software and purposive sampling with a sample size of 100 consumers. Implications: Businesses should prioritize service quality, pricing strategies, and customer satisfaction to foster customer loyalty and enhance competitiveness. Keywords: Service Quality, Price, Customer Satisfaction, Customer Loyalty, Retail Study